Vorarephilia: A Case Study in Masochism and Erotic Consumption. - Lykins, Amy; Cantor, James (Archives of Sexual Behavior, 2014)
Vorarephilia ('vore') is an infrequently presenting paraphilia, characterized by the erotic desire to consume or be consumed by another person or creature. Few data exist on vore though several cases have been reported which appear to be consistent with basic vorarephilic interests. Because this sexual interest cannot be enacted in real life due to physical and/or legal restraints, vorarephilic fantasies are often composed in text or illustrations and shared with other members of this subculture via the Internet. Similarities with aspects of bondage/dominance sadomasochism interests, more specifically dominance and submission, are noted. The current case report describes a man with masochistic sexual interests which intersected with submissive vorarephilic fantasy.